PERFORMANCE LABOR IN AGRICULTURE SECTOR IN JAVA ISLAND USING PANEL DATA 2007-2014 - Joko Pranoto; Agung Priyo Utomo; Muhamad Fathul Muin (Universitas Tadulako, 2020)
The highest decrease in the number of food crop workers occurred in Java, as many as 2,87 million people in 2007-2014. The age of food crop agriculture workers in Java is dominated by workers aged over 45 years (64,95%). If there is no addition of new workers, then the food crop labor will be increasingly dominated by old age groups which will make it difficult for the agricultural sector to carry out its mandate to improve and maintain sustainable food security. The purpose of this study is to describe the condition of the food crop agriculture subsector from the aspect of labor absorption in Java for the period 2007-2014 and analyze the effect of the regional GDP of food crops subsector, real wages, education, and land area to the absorption power of agricultural food crops subsector on labor in Java. Central Java Province is a province with the largest decrease in the number of agricultural food crop subsector workers compared to the other four provinces on Java island. From the results of the estimation, the fixed-effect model with cross-section SUR is chosen as the best model. The results show that the variable of regional GDP, real wage, and size of land area has a significant and positive effect on the labor absorption of agricultural food crops subsector, while education has a significant and negative effect. Overall this model able to explain variations of this phenomenon by 89,32%. Meanwhile, another 10,68% is explained by other variables not included in the model.